The current situation of small ruminant enterprises of burdur province - Özkan Elmaz; Özgecan Korkmaz Ağaoğlu; Aykut Asım Akbaş; Mustafa Saatcı; Mehmet Çolak; Mahiye Özçelik Metin (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to determine the present situation of small ruminant enterprises of Burdur province in the West Mediterranean region of Turkey known as “Goat Region” Materials and Methods: Research data obtained from farmer by face to face questionnaires. Data were collected from 48 goats and 64 sheep enterprises at 32 villages and town. The questionnaire contained five main sections: demographic data about the enterprise; the enterprise's housing and landscaping; data about the feed and feeding methods used in the enterprises; milk production and hygienic criteria in the enterprises and farm management. Results: The average number of sheep and goat per enterprise were found 94.8 and 117.8 heads respectively. It was determined that sheep and goat breeders graduated from primary school at the rates of 85.9% and 77.2% respectively. Examined sheep enterprises 84.4% was semi-open type barn. This rate was 70.4% in goat enterprises. Duration of suckling period of lambs in sheep enterprises were between 4 to 6 months, kids suckling period ranged between 4 and 7 months in goat enterprises. In this research average milk yield was found in sheep and goat enterprises in 32 villages; 0.5±0.09 l/day/sheep and 0.5±0.3 l/day/goat, respectively. Conclusions: This research was the first study to demonstrate the current status of small ruminant enterprises of Burdur province in the Mediterranean region of Turkey. It is thought that the results of this research will form important database for future research about development of sheep and goat farming in Burdur province of Turkey